Development of Android Application-Based Early Childhood Learning Devices (PAUDPEDIA) During the COVID-19 Pandemic - Nurhasanah, Nia; Masitoh, Siti; Arianto, Fajar; Ayubi, Novadri (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Early Childhood Education has an important role in the development of a child. When talking about Early Childhood Education quality is the most critical, especially during the Covid-19 Pandemic as it is today and coincides with the era of the industrial revolution 4.0 where the education system underwent drastic changes. This study aims to (1) produce an Early Childhood Education application based on android; (2) test the effectiveness of the Early Childhood Education application. The development of the Android-based PAUDPEDIA application will be carried out using the 4D Model Research and Development method proposed by Thiagarajan and Semmel. This research and development are divided into four stages, namely define, design, develop, and disseminate. The results of this study indicate that researchers can achieve the expected output targets, namely (1) the results of the expert trial of the Android-based PAUDPEDIA Application showed a percentage of 86.7%. This means that the Android-based PAUDPEDIA Application is very feasible to be distributed to users and ready to use; while the results of user trials on the Android-based PAUDPEDIA application showed a percentage of 86.2%. This means that the Android-based PAUDPEDIA Application is effective for use by users; and (2) the Android-based PAUDPEDIA application is effective to be used to facilitate distance education activities in Early Childhood Education. It can be concluded that the Android-based PAUDPEDIA application is very suitable for use by users and is effectively used for distance education activities in PAUD, especially during the current COVID-19 pandemic.